A critique of financial education in mathematics education - Sachs, Línlya [UNESP]; Viel Gereti, Laís Cristina; Ferraiol, Thiago Fanelli; Elias, Henrique Rizek [UNESP]; De Souza, Luiza Gabriela Razêra (FapUNIFESP (SciELO), 2023)
This paper aims to present a critique of financial education in Mathematics Education, through a systematic literature review. Based on a Marxist theoretical foundation, it is considered that carrying out a critique of financial education presupposes an understanding of the capitalist system itself and its ideological aspects. Thus, a bibliographic survey of articles dealing with the subject of financial education was carried out in all available volumes of 51 journals chosen until the year 2021. 229 papers were found in 37 journals, with the first publication dating from 2007. For the analyses, we used categories created a posteriori, that is, from the reading of the texts collected. The results show that, on the one hand, five articles (2.2%) criticize the capitalist system, 47 (20.5%) aspects of the system, and 174 (76%) do not criticize it and, on the other hand, one article (0.4%) presents some kind of revolutionary proposition, eight (3.5%) reformist propositions, 74 (32.3%) behavioral propositions, 106 (46.3%) instrumental propositions, and 66 articles (28, 8%) are non-propositional. The panorama of research in financial education points to the need for investigations that address the topic based on scientific knowledge, especially the social sciences, such as economics and sociology. The near absence of theoretical bases in these areas in the analyzed corpus may indicate a fragility of Mathematics Education research, because, despite being based on scientific assumptions specific to the educational field, they promote ideological discourses of financial institutions, which have profit as their objective.
Crítica da educação financeira na educação matemática
Keywords: Capitalism; Financial Education; Marxism; Mathematics Education; Systematic Review of Literature